The role of lipid metabolism in immune thrombocytopenia: new perspectives from immune inflammation and thrombopoiesis - Dan Li; Luer Qiu; Ying Zhang; Li Hong; Sai Zhou; Weiying Feng (Journal of Translational Medicine, 2026)
Abstract Background Primary immune thrombocytopenia (ITP) is an autoimmune condition defined by increased immune-driven platelet destruction and inadequate platelet generation. Emerging research highlights that global alterations in lipid metabolism are closely associated with immune dysfunction and suppressed thrombopoiesis in ITP, offering a new metabolic framework for understanding disease mechanisms. Main body This review provides a comprehensive analysis of the pivotal role played by lipid metabolic pathways in the development and progression of ITP. Dysregulated lipid metabolism—characterized by upregulated fatty acid biosynthesis and diminished oxidative metabolism—promotes the expansion of pro-inflammatory T helper cells (Th1/Th17), activates B cells and M1 macrophages, and simultaneously undermines the suppressive activity of regulatory T cells (Tregs) and anti-inflammatory M2 macrophages. Such metabolic imbalances lead to chronic inflammation and accelerate platelet elimination. In addition, disturbances in lipid homeostasis negatively affect megakaryocyte differentiation and compromise platelet membrane stability, thereby further inhibiting platelet production. We also examine potential therapeutic interventions targeting lipid-related pathways, such as boosting the synthesis of specialized pro-resolving mediators, modulating immune cell metabolic programming, utilizing existing lipid-lowering drugs (e.g., statins) for new indications, and applying dietary modifications to influence disease outcomes. Conclusions Altered lipid metabolism may represent a central immunometabolic axis linking immune dysregulation and impaired thrombopoiesis in ITP. Combining lipid-targeted approaches with standard immunomodulatory treatments may open new avenues for treating patients with refractory ITP. Further research into lipidomic signatures and underlying molecular mechanisms is needed to advance these findings toward clinical application.